Sostenibilidad social de una radio comunitaria: El caso de Radio Latacunga. - Valverde Quinatoa, Darío Xavier (2020)
Community radio in Ecuador has been a tool used to express needs, culture, and information democratically and, at the same time, strengthening the mutual commitment to social groups. However, currently, the social sustainability of a community radio medium has both external and internal factors to be effective, putting volunteering as a relevant factor for the existence of social sustainability in a community radio environment and thus contributing to the essence of what It represents community radio. The present research project based on this background was developed in Radio Latacunga, which belongs to the Latacunga Canton of the Cotopaxi Province, and it considers identifying the dynamics that have contributed to the social sustainability of Radio Latacunga. The methodology that was proposed in the research project was quantitative and qualitative; a survey was carried out on people who listen to Radio Latacunga, from which the empowerment by people towards the community radio medium was visualized. An interview was conducted with two people specialized in community radios and a focus group of Radio Latacunga collaborators, which highlights that the sustainability of Radio Latacunga is due to the following causes: Volunteering as a factor that contributes to the social sustainability of Radio Latacunga, in addition to the close relationship between social sustainability and economic sustainability. When determining the factors that contribute to the social sustainability of Radio Latacunga, we verify that social sustainability exists in this community radio medium.